Gambaran Pengetahuan dan Sikap Ibu Hamil tentang Pemberian ASI Eksklusif : Knowledge and Attitudes about Exclusive Breastfeeding among Pregnant - Fransisca Noya; Nining Supriyani Maliusi; Nurfatimah Nurfatimah; Lisda Widianti Longgupa; Christina Entoh (Poltekkes Kemenkes Palu, 2021)
Introduction: Providing exclusive breastfeeding for the first six months old has many advantages both for baby and mother. Lack of mother knowledge concerning exclusive breastfeeding can affect the mother's attitude towards exclusive breastfeeding. Exclusive breastfeeding coverage in Tegalrejo Village in 2016 was 69%. It decreased in 2017 to 52%, then decreased again in 2018 to 44%. Exclusive breastfeeding coverage in Tegalrego Village has not fulfilled the Poso Regency Government standard which is 50%. This study aims to describe the knowledge and attitudes of pregnant women about exclusive breastfeeding. Methods: This research used descriptive quantitative method. The study population were all pregnant women who live in Tegalrejo Village totaling 33 mothers. The sample was taken using total sample technique. Results: from 33 respondents there were 20 respondents with good knowledge, and 28 respondents with positive attitude. Conclusion: It can be concluded that mainly respondents have a good knowledge and positive attitude towards exclusive breastfeeding